Legal Review of a Man who has Sexual Intercourse with a Woman so that He has a Child Out of Wedlock (Case Study of North Sumatra Police Report Number: STTLP/B/559/X/2024/SPKT/POLDA SUMUT) - David Angdreas (SEAN Institute, 2025)
Sexual intercourse outside the bonds of legal marriage is a complex phenomenon with profound legal and social implications, especially when it results in children out of wedlock. In the Indonesian legal context, this act is known as adultery or extra-marital copulation, and has significant consequences, particularly in relation to the legal status of the child and the rights attached to it. In this research, the research method used is non-research qualitative research. Results of Research and Discussion: Police efforts in conducting DNA tests to biological fathers and legal protection for victims (children) of intercourse in review of Law Number 35 of 2014. The conclusions and suggestions in this study are that police efforts in establishing biological fathers through DNA testing are important procedures in criminal investigations, supported by the Criminal Procedure Code and the Child Protection Law, despite facing cost, consent, privacy, and psychological challenges; meanwhile, Law No. 35 of 2014 provides strong legal protection for children from the results of adultery based on the principle of non-discrimination, guaranteeing their basic rights even though proving the relationship of biological fathers and related civil rights is still a challenge. To optimise the use of DNA testing by the police and the legal protection of children from adultery in accordance with Law Number 35 of 2014, clear SOPs, adequate budget, strong coordination, increased officer capacity, data privacy guarantees, psychological considerations, cross-agency cooperation, socialisation of the Constitutional Court Decision, effective paternity proof mechanisms, increased paternal responsibility, harmonisation of civil law, empowerment of mothers and children, and evaluation of the implementation of the law are needed.